Vaccinomics: a cross-sectional survey of public values. Issue 9 (2nd September 2021) - Gerber, Jennifer E.; Brewer, Janesse; Limaye, Rupali J.; Sutherland, Andrea; Blunt, Madeleine; Holroyd, Taylor A.; Geller, Gail; Carleton, Bruce; Kahn, Jeffery; Salmon, Daniel A.
ABSTRACT: Objective : We characterize public values regarding vaccinomics, which aims to improve vaccine safety and effectiveness using genomics. Methods: Panel survey (2020) of ≥18-year-olds with embedded animation introduced vaccinomics. Sociodemographic, health, and vaccination-related items were adapted from validated scales. Novel items measured trust in public health authorities, vaccinomics-related values, and preferences for federal funding: vaccinomics compared with vaccine issues and chronic diseases. Beginning and end of survey confidence in vaccine safety was measured to assess potential changes. Data were weighted to the U.S. Census. Vaccinomics-related concerns were stratified by sociodemographic characteristics, vaccine hesitancy status (composite outcome), reported serious vaccine reactions, and trust in public health authorities (PHA). Log binomial regression models estimated associations between these variables and agency to make vaccine-related decisions. Results: Most (70.7%, N = 1, 925) respondents expected vaccinomics would increase their vaccine confidence compared to now. Agreement was highest among those without serious vaccine reaction experience (unexperienced: 74.2% versus experienced: 62.3%), with high trust in PHA (high: 83.3% versus low: 57.4%), and low vaccine hesitancy among parents of teenagers (low: 78.8% versus high: 62.5%) and adults without minor children (low: 79.8% versus high: 60.6%; all p < .01). Belief that vaccination was an individual's choice was associated with reported serious reactions (adjusted Prevalence Ratio (aPR): 1.16; 95% CI: 1.07, 1.25) and low trust (aPR: 0.91; 0.84, 0.98). Beginning versus end of survey vaccine safety perceptions were similar. Conclusion: Federal funding, communications, and policies should assure the public that vaccinomics will not remove their decision–making power and engender trust in PHA.